Cholinergic neurons—keeping check on amyloid β in the cerebral cortex - Ovsepian, Saak V.; Herms, Jochen (Frontiers in Cellular Neuroscience, 2013)
The physiological relevance of the uptake of ligands with no apparent trophic functions via the p75 neurotrophin receptor (p75NTR) remains unclear. Herein, we propose a homeostatic role for this in clearance of amyloid β (Aβ) in the brain. We hypothesize that uptake of Aβ in conjunction with p75NTR followed by its degradation in lysosomes endows cholinergic basalo-cortical projections enriched in this receptor a facility for maintaining physiological levels of Aβ in target areas. Thus, in addition to the diffuse modulator influence and channeling of extra-thalamic signals, cholinergic innervations could supply the cerebral cortex with an elaborate system for Aβ drainage. Interpreting the emerging relationship of new molecular data with established role of cholinergic modulator system in regulating cortical network dynamics should provide new insights into the brain physiology and mechanisms of neuro-degenerative diseases.